Desenvolvimento de metodologia para a determinação de farmácos sintéticos em formulações fitoterápicas emagrecedoras empregando eletroforese capilar - Martini, Mariele (2010)
The adulteration of phytotherapeutic formulations used for weight loss with synthetic pharmaceuticals has been increasing in recent years. The cases of adulteration have been reported in the literature, showing that there is a great concern about this problem, which involves the development of analytical methodologies able to detect them. This paper describes the development of a method for the simultaneous determination of amfepramone, fenproporex, sibutramine and fluoxetine by using capillary zone electrophoresis (CZE) with capacitively coupled contactless conductivity detection (C4D) in a homemade capillary electrophoretic system. The optimized conditions for separation of the pharmaceuticals by CZE-C4D were the following: 50 mmol L-1 phosphate buffer (pH 5.0) containing acetonitrile 50% (v/v) as working electrolyte, separation potential of -15 kV, separation temperature of 25 °C, hydrodynamic injection by gravity (20 cm left side elevation for 60 s). The C4D detection was performed by using a homemade detector, which employs a sinusoidal wave generator operating at 600 kHz frequency and 2 Vpp wave amplitude. The CZE-C4D method was validated for the determination of amfepramone, fenproporex, sibutramine and fluoxetine and it was applied to the analysis of phytotherapeutic formulations used for weight loss, which have been purchased in different commercial pharmacies in the city of Santa Maria. This method was fit in the analysis of four synthetic drugs studied, with a wide linear response range (10 to 500 mg L-1), low detection limits (4 to 5 mg L-1), precision (6 to 9 %) and accuracy (95 to 112 %) . The recovery experiments were carried out in the samples and the recovery values ranged between 80 and 120 % for all the studied samples. The developed method showed high sensitivity, selectivity and analytical precision and it can be used for determining these substances as contaminants in herbal natural formulations. It also an important alternative to the federal control agencies due to its simplicity, rapidity and low cost of analysis considering the small quantities of reagents and samples used.